Interaction of ArmZ with the DNA-Binding Domain of MexZ Induces Expression of mexXY Multidrug Efflux Pump Genes and Antimicrobial Resistance in Pseudomonas aeruginosa - Kawalek, Adam (Antimicrob Agents Chemother, 2019)
Multidrug efflux pumps play an important role in antibiotic resistance in bacteria. In Pseudomonas aeruginosa, the MexXY pump provides intrinsic resistance to many antimicrobials, including aminoglycosides. The expression of the mexXY operon is negatively regulated by the MexZ repressor. This repression is alleviated in response to antibiotic-induced ribosome stress, which results in increased synthesis of the antirepressor ArmZ, interacting with MexZ. The molecular mechanism of MexZ inactivation by ArmZ is not known. Here, we show that the N-terminal part of MexZ, encompassing the DNA-binding domain, is required for the interaction with ArmZ. Using bacterial two-hybrid system-based mutant screening and pulldown analyses, we identified substitutions in MexZ that diminished (R3S, K6E, and R13H) or completely impaired (K53E) the interaction with ArmZ without blocking MexZ activity as a transcriptional repressor. The introduction of the corresponding mexZ missense mutations into the P. aeruginosa PAO1161 chromosome impaired (mexZ(K6E) and mexZ(R13H)) or blocked (mexZ(K53E)) tetracycline-mediated induction of mexY expression. Concomitantly, the PAO1161 mexZ(K53E) strain was more susceptible to aminoglycosides. The identified residues are highly conserved in MexZ-like transcriptional regulators found in bacterial genomes encoding both MexX/MexY/MexZ and ArmZ/PA5470 orthologs, suggesting that a similar mechanism may contribute to the induction of efflux-mediated resistance in other bacterial species. Overall, our data shed light on the molecular mechanism of ArmZ-mediated induction of intrinsic antimicrobial resistance in P. aeruginosa.